Production of (anti-)He-3 and (anti-)H-3 in p-Pb collisions at √s(NN)=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; Ohlson, Alice; et al. (Physical review, 2020)
The transverse momentum (p(T)) differential yields of (anti-)He-3 and (anti-)H-3 measured in p-Pb collisions at root s(NN) = 5.02 TeV with ALICE at the Large Hadron Collider (LHC) are presented. The ratios of the p(T)-integrated yields of (anti-)He-3 and (anti-)H-3 to the proton yields are reported, as well as the pT dependence of the coalescence parameters B-3 for (anti-)He-3 and (anti-)H-3. For (anti-)He-3, the results obtained in four classes of the mean charged-particle multiplicity density are also discussed. These results are compared to predictions from a canonical statistical hadronization model and coalescence approaches. An upper limit on the total yield of (4)(He) over bar is determined.
Im Titel ist "3" hochgestellt und "pp" schräg gestellt
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
Gesehen am 22.07.2020
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, A. Yüncü [und 977 weitere]